In professional road cyclists, low pedaling cadences are less efficient - Lucia, A.; San Juan, A. F.; Montilla, M.; CaNete, S.; Santalla, A.; Earnest, C.; Perez, M. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: To determine the effects of changes in pedaling frequency on the gross efficiency (GE) and other physiological variables (oxygen uptake (VO2), HR, lactate, pH, ventilation, motor unit recruitment estimated by EMG) of professional cyclists while generating high power outputs (PO). METHODS: Following a counterbalanced, cross-over design, eight professional cyclists (age (mean +/- SD): 26 +/- 2 yr, VO2max: 74.0 +/- 5.7 mL x kg x min) performed three 6-min bouts at a fixed PO (mean of 366 +/- 37 W) and at a cadence of 60, 80, and 100 rpm. RESULTS: Values of GE averaged 22.4 +/- 1.7, 23.6 +/- 1.8 and 24.2 +/- 2.0% at 60, 80, and 100 rpm, respectively. Mean GE at 100 rpm was significantly higher than at 60 rpm (P < 0.05). Similarly, mean values of VO2, HR, rates of perceived exertion (RPE), lactate and normalized root-mean square EMG (rms-EMG) in both vastus lateralis and gluteus maximum muscles decreased at increasing cadences. CONCLUSIONS: In professional road cyclists riding at high PO, GE/economy improves at increasing pedaling cadences.